A influência da alavancagem financeira na construção do custo de capital próprio: um estudo voltado para o mercado brasileiro - Terenzi, Victor Eduardo (2016)
In the context of the Capital Asset Pricing Model (CAPM), the present study investigates the significance of financial leverage on the development of systematic risk. Based on Brazilian data, we tested the beta unleveraged and leveraged process, widely used by practitioners in order to compute the cost of equity capital for non-traded firms. Our results suggest that including tax shields in the unleverage/leverage formula and the use of market data led to more robust information, while the industry sectors have little capacity to determine systematic risk classes.